RE-DESAIN KEMASAN PRODUK RENDANG TELUR KOKOCI DI NEGARI VII KOTO TALAGO , KECAMATAN GUGUAK, KAB. 50 KOTA - RIEHAN DERMAWAN, Dr. Syafwandi, M.Sn., Dini Faisal, S.Ds., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The development of small and medium industries is one of the backbone of national economic development. One of the home industry is Rendang telur. Typical food from Jorong Koto Kociak, VII Koto Talago, Guguak, Kab. 50 This city, made of cassava of choice and has a delicious taste and tasty. Rendang Egg Kokoci still do not have a decent and interesting packaging, because the new form of plastic glass plastic. While other Rendang Egg industries already exist that use packaging that attract buyers attention. This final work aims to produce an interesting design design of the typical Rendang Telok Kokoci food package Koto Kociak, Kab.50 Kota. With the design of food packaging packaging of typical Koto Kociak Kokoci Eggs, Kab.50 The city is expected to attract the attention of buyers or the wider community so as to increase sales.Keywords: Packaging, Rendang Egg Kokoci, Design.